1975
DOI: 10.1159/000180501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Correction of Metabolic Acidosis on Bone Mineralisation Rates in Patients with Renal Osteomalacia

Abstract: The role of metabolic acidosis in the genesis of renal osteomalacia was investigated by studying bone mineralisation and resorption rates with a combined isotope and balance technique in six patients, before and after the administration of alkali. Correction of blood pH was achieved in five cases and was associated with a significant rise in the bone mineralisation rates and a significant positive trend in the calcium balances. It is suggested that acidosis contributes to the pathogenesis of osteomalacia in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Chronic metabolic acidosis is common in advanced stages of CKD, and it is associated with adverse consequences, including increased mortality, acceleration of kidney disease progression, increased muscle breakdown and insulin resistance, and the development or exacerbation of bone disease (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Clinical evidence shows that treatment of low serum bicarbonate can improve kidney, muscle, bone, and nutritional sequelae of chronic metabolic acidosis (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic metabolic acidosis is common in advanced stages of CKD, and it is associated with adverse consequences, including increased mortality, acceleration of kidney disease progression, increased muscle breakdown and insulin resistance, and the development or exacerbation of bone disease (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Clinical evidence shows that treatment of low serum bicarbonate can improve kidney, muscle, bone, and nutritional sequelae of chronic metabolic acidosis (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…In-vivo rat studies have also shown the stimulation of cell-mediated bone resorption during prolonged acidosis [34,48]. Further support for bone buffering the acid load comes from studies of acidosis patients in which the bone mineral loss could be corrected by bicarbonate ion administration [49][50][51].…”
Section: In-vivo Observationsmentioning
confidence: 99%
“…The current standard is the result of a compromise between the advantages of normalizing pre-dialysis acidosis and the side effects of the transient peri-and post-dialysis alkalosis resulting from bicarbonate transfer. The adverse consequences on the one hand of persistent metabolic acidosis on bone metabolism [3][4][5] and nitrogen balance [6,7] and on the other of transient metabolic alkalosis on neuromuscular excitability and on cerebral blood fl ow (inducing paresthesias, twitching and cramping) [8][9][10] are well established. Furthermore, the positive inotropic effect induced by alkalemia in experimental models [11,12] seems to be at least in part counterbalanced by the resultant reduction in ionized calcium in serum [13] .…”
mentioning
confidence: 99%